Native knowledge of great lakes ecology: Climate changes to Odawa lands - Stoffle, Richard W.; Evans, Michael J.; Sittler, Christopher; Berry, Desmond L.; Van Vlack, Kathleen A. (Frontiers in Climate, 2023)
Climate change has been observed for hundreds of years by the plant specialists of three Odawa Tribes in the Upper Great Lakes along Lake Michigan. Sleeping Bear Dunes National Lakeshore is the focus of two National Park Service (NPS) studies of Odawa Traditional Ecological Knowledge (TEK) of plants, ecosystems, and climate change. Data collected during these studies contributed to developing Plant Gathering Agreements between tribes and parks. This analysis derived from 95 ethnographic interviews conducted by University of Arizona (UofA) anthropologists in partnership with tribal appointed representatives. Odawa people recognized in the park 288 plants and five habitats of traditional and contemporary concern. Tribal representatives explained that 115 of these traditional plants and all five habitats are known from multigenerational eyewitness accounts to have been impacted by climate change. The TEK study thus represents what Native people know about the environment. These research findings are neither intended to test their TEK nor the findings of Western science.